(untitled) (Bangladesh Journal of Urology, 2022)
Cystic renal tumors often create diagnostic dilemma. It might be a cancer in a complex cyst, cystic degeneration of a renal cell carcinoma, Papillary cystic renal cell carcinoma or multilocular cystic renal cell carcinoma (MCRCC). MCRCC is a rare cystic tumor of the kidney. It is recognized as a separate subtype of renal cell carcinoma in WHO classification of adult renal tumors in 2004 with excellent prognosis. A 47 years old male presented with an incidentally detected large right renal cystic lesion in the upper and hilar region. After discussion with the patient about the possibilities, right radical nephrectomy was performed. Histopathology was done by one of the renowned Pathologists of the country and was reported as a rare variety Multilocular Cystic Renal Cell Carcinoma. It is very important to differentiate this type of cystic renal cell carcinoma from cystic degeneration of conventional RCC. Bangladesh J. Urol. 2021; 24(2): 224-228